HUKUM KELUARGA ISLAM: Perspektif Maqāṣid asy-Syarīah Terhadap Dasar Wajib Patuh Pada Undang-undang Perkawinan dan Kompilasi Hukum Islam - Nur Rofiq; Moh Tamtowi; Rahmawati; M. Nashih Muhammad; Ahmad Asroni; Kuswan Hadji (Wahana Islamika Jurnal Studi Keislaman, 2023)
The State of Indonesia is a state based on law, so for Indonesian people who are Muslim when they enter into a marriage, they must obey and comply with the Marriage Law (UUP) and the Compilation of Islamic Law (KHI), because UUP and KHI are legal products resulting from the government's (leader) ijtihad in regulating marital problems in Indonesia. The purpose of this study is to understand and analyze the obligation to comply with the Marriage Law and the Compilation of Islamic Law from the perspective of maqashid sharia. The research method used uses a descriptive-qualitative approach, with the type of library research with data sources based on Presidential Instruction (Inpres) No. 1 of 1991 concerning the Compilation of Islamic Law (KHI) and Law Number 1 of 1974 concerning Marriage (UUP) and materials -Other library materials. The results of this study prove that the basic obligation to comply with the Marriage Law (UUP) and the Compilation of Islamic Law (KHI) is because both are products of government ijtihad (ulil amri). The government's ijtihad is a manifestation of the thoughts and agreements of all the Indonesian people who have been represented by the DPR. So that the obligation to comply with UUP and KHI in the perspective of Maqashid Sayariah is mandatory because it brings benefit and avoids harm. The marital status of husband and wife and children born are legal and protected by law.